Marker assisted backcross breeding for pyramiding genes conferring resistance to bacterial blight in rice variety uma - Megha L M (Department of Plant Breeding and Genetics, College of Horticulture, 2018)
As in other rice growing locales around the world, bacterial blight (BB) caused by Xanthomonas oryzae pv. oryzae (Xoo) assumes a huge role in deciding rice profitability in Kerala. The elite rice varieties of Kerala, both PTB 39 (Jyothi) and Mo 16 (Uma), are found to be extremely susceptible to bacterial blight. Since both the major rice cropping seasons (virippu and mundakan) in the state coincide with monsoons, the control of the disease through chemicals or biological agents proves inadequate owing to the washing-off of the applied materials. Host-plant resistance is advocated as the most effective breeding strategy to combat the bacterial blight (BB) pathogen. Considering the impact of the disease on food security and sustainability, efforts were taken to introgress three R-genes (xa5, xa13 and Xa21) into the variety Uma from donor parent Improved Samba Mahsuri (ISM) through Marker Assisted Selection (MAS). Further, backcrossing to Uma (recurrent parent) and advancing the resultant BC1F1s have resulted in production of BC2F1 generation (21 Nos.). The present study aimed to identify BC2F1 plants pyramided with genes (xa5, xa13 and Xa21) conferring resistance to bacterial blight using functional markers. In addition, advancing the R-gene introgressed BC2F1s to BC3F1 and BC2F2 generation was envisaged. Pathotyping of BC1F2s (850 Nos.) and generating BC1F3s from the plants exhibiting resistance to BB pathogen was also aimed at. Foreground selection of the BC2F1 individuals using the xa5 gene linked STS marker RG 556 and functional marker xa5 SR confirmed the presence of the R-gene in the parents as well as the 21 BC2F1 individuals. Screening of BC2F1 individuals with STS marker RG 136 linked to R-gene xa13 and functional marker xa13 promoter revealed that the BC2F1 Plant No. 8.3.9.10 was heterozygous at xa13 locus while, all other BC2F1 individuals possessed alleles similar to that of the recurrent parent (RP) Uma. The result also pointed out that BC2F1 Plant No. 8.3.9.10 was a 2-R-gene pyramid (xa5xa5 + Xa13xa13). Foreground selection with STS marker pTA 248 to detect the presence of Xa21 gene revealed that none of the BC2F1 plants analysed except BC2F1 Plant No. 8.3.9.10, possessed the resistant allele of R-gene Xa21. However, presence of alleles of both the parents in Plant No. 8.3.9.10 indicated that it was heterozygous at Xa21 locus. Results obtained thus revealed that, of the 21 BC2F1s subjected to foreground selection, BC2F1 Plant No. 8.3.9.10 was the only 3-R-gene introgressed pyramid (xa5xa5 + Xa13xa13 + Xa21xa21). In addition, the 3-R-gene introgressed BC2F1 Plant No. 8.3.9.10 was subjected to background screening using 22 rice microsatellite (RM) markers. Background profiling revealed that the banding pattern in Plant No. 8.3.9.10 was similar to recurrent parent in case of thirteen RM markers. The plant was found to be heterozygous at five other marker loci. Considering the segregation of the 22 markers, the magnitude of recovery of recurrent parent genome in 3-R-gene introgressed BC2F1 Plant No. 8.3.9.10 was found to be 81.82 per cent. The dendrogram based on molecular data grouped the individuals into two major clusters. Cluster 1 was monogenic with only the donor parent ISM and cluster 2 comprised of the recurrent parent Uma and Plant No.8.3.9.10, further suggesting that the 3-R-gene introgressed BC2F1 Plant No. 8.3.9.10 was more similar to the recurrent parent Uma. Wide variability was observed among the BC2F1 individuals for various morphological traits. The 3-R-gene introgressed BC2F1 Plant No. 8.3.9.10 was shorter in duration than both the parents and also possessed red kernels similar to the recurrent parent Uma. The dendrogram generated based on the morphological characters also indicated greater similarity between the 3-R-gene pyramid and recurrent parent Uma. The identified 3-R-gene pyramid (BC2F1 Plant No. 8.3.9.10) was backcrossed to both recurrent parent Uma as well as selfed resulting in production of BC3F1s (15 Nos.) and BC2F2s (28 Nos.) respectively. Bioassay of BC1F2 population (106 Nos.) through leaf clipping method of pathotyping suggested by IRRI (1991) revealed that more than half the BC1F2 individuals screened exhibited resistance to BB pathogen. The plants that exhibited moderate reaction to BB infection ranged between 16.87 per cent and 34.78 per cent in progeny of BC1F2 Plant No. 8.3.2 and BC1F2 Plant No. 8.3.9 respectively. Selfing of the BC1F2 individuals exhibiting resistance and moderate resistance to BB pathogen resulted in production of 725 BC1F3 seeds. Modern molecular techniques make it possible to use markers and probes to track the simultaneous introgression of several R-genes into a single cultivar during a crossing programme. Foreground and background profiling of backcross generations can ensure precise identification of R-gene introgressed genotypes that resemble the recurrent parent Uma.